Comparative sensitivity and specificity of serological tests (Colombia Medica, 1993)
Using 313 sera from normal individuals and patients with a variety of illnesses and conditions as well as untreated syphilis with different clinical stages, specificity and sensitivity of the VDRL, RPR, Ff A-ABS, TPHA, and lgM-TP-ELISA assay for Treponema pallidum, were compared. Results gave incidences of false-positive reactions of 24.5%, 11.9%, 5.3%, 2.4%, and 0.6%, respectively. The whole sensitivities found were 78.3%, VDRL; 84.5%, RPR; 95.3%, Ff A-ABS; 90.5%, TPHA; and 98%, lgM-TP-ELISA. The lgM-TP-ELISA assay seems to be an appropriate method for detecting acute or subacute T. pallidum infections and a valuable tool for judging false positive reactions.